2022
DOI: 10.1182/bloodadvances.2022008632
|View full text |Cite
|
Sign up to set email alerts
|

Enasidenib as maintenance following allogeneic hematopoietic cell transplantation for IDH2-mutated myeloid malignancies

Abstract: IDH2 (isocitrate dehydrogenase 2) mutations occur in approximately 15% of patients with acute myeloid leukemia (AML). The IDH2 inhibitor enasidenib was recently approved for IDH2-mutated relapsed or refractory AML. We conducted a multi-center, phase I trial of maintenance enasidenib following allogeneic hematopoietic cell transplantation (HCT) in patients with IDH2-mutated myeloid malignancies. Two dose levels, 50mg and 100mg daily were studied in a 3x3 dose-escalation design, with 10 additional patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…16 Promising results with ivosidenib were seen in a phase 1 trial. 17 These real-life data confirm the efficacy and good safety profile of ivosidenib as a single agent in relapsed AML after alloHCT, with excellent deep and durable responses in some patients. Data are needed to identify patients most likely to respond and other studies evaluating ivosidenib in combination with other treatments such as hypomethylating agents and in the posttransplant setting as a maintenance therapy are ongoing.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…16 Promising results with ivosidenib were seen in a phase 1 trial. 17 These real-life data confirm the efficacy and good safety profile of ivosidenib as a single agent in relapsed AML after alloHCT, with excellent deep and durable responses in some patients. Data are needed to identify patients most likely to respond and other studies evaluating ivosidenib in combination with other treatments such as hypomethylating agents and in the posttransplant setting as a maintenance therapy are ongoing.…”
supporting
confidence: 63%
“…Finally, the use of ivosidenib as a maintenance post‐alloHCT would be an interesting strategy for relapse prevention, following the example of FLT3‐targeted therapies 16 . Promising results with ivosidenib were seen in a phase 1 trial 17 …”
Section: Figurementioning
confidence: 99%
“…In this study, the benefit of MRD-negativity on OS was similar at across various time points between one and 4 months, demonstrating prognostic value of late MRD clearance [81]. In another retrospective series, of patients who achieved CR with either HMA/Ven or IC, MRD negativity was achieved in approximately 80% of patients in both arms [79].…”
Section: Hypomethylating Agents With Venetoclax and Mrdmentioning
confidence: 68%
“…In both DTA and non-DTA ddPCR targets, MRD negativity at the 3-month follow-up was significantly prognostic for transplantation outcome. As targeted maintenance therapies emerge, [32][33][34] this feature might serve as a valuable tool for response evaluation and optimal application. This finding seems to conflict with Heuser et al 35 who only found a prognostic impact of non-DTA mutations, but no prognostic impact of DTA mutations post-transplantation.…”
Section: Ddpcr Target Eliminationmentioning
confidence: 99%